Prestation vid sönderdelning av GROT med olika typer av maskiner - Karlsson, Daniel (2010)
There is a need for productivities data and data for different types of machines for comminution of logging residues. The lack of data and studies on GROT comminution makes it difficult to evaluate different chains for handling of residue fuels and make system analyses.